Polymer film formation in cement mortars modified with water-soluble polymers. (April 2015) - Knapen, E.; Van Gemert, D.
Abstract: The modification of cement mortars with small amounts of water-soluble polymers (polyvinyl alcohol-acetate, methylcellulose and hydroxyethylcellulose) is studied. During hardening, two processes can take place, i.e. cement hydration and polymer film or bridge formation. Due to the very low polymer contents, the formation of polymer films is generally not considered. In this paper, evidence is given of the presence of polymer films or bridges in mortars modified with 1% of polyvinyl alcohol-acetate or methylcellulose. A contribution to the flexural strength of these mortars is found. By means of SEM investigation, polymer bridges are detected between the layered Ca(OH)2 crystals. Additional bonds are created which strengthen the preferential cleavage sites. Furthermore, polymer films or bridges are intergrown within the cement matrix on a submicron scale.